New arrangements on several species subcomplexes of Triatoma genus based on the chromosomal position of ribosomal genes (Hemiptera - Triatominae) - Pita, Sebastián; Lorite, Pedro; Nattero, Julieta; Galvão, Cleber; Alevi, Kaio C.C. [UNESP]; Teves, Simone C.; Azeredo-Oliveira, Maria T.V. [UNESP]; Panzera, Francisco (Elsevier, 2016)
The hemipteran subfamily Triatominae includes 150 blood-sucking species, vectors of Chagas disease. By far the most specious genus is Triatoma, assembled in groups, complexes and subcomplexes based on morphological similarities, geographic distribution and genetic data. However, many molecular studies questioned the species integration of several subcomplexes as monophyletic units. In triatomines, chromosomal position of major ribosomal DNA (rDNA) loci is extremely variable but seems to be species-specific and an evolutionary conserved genetic trait, so that closely related species tend to have ribosomal clusters in the same chromosomal location. Considering that the autosomal position as the ancestral character for all heteropteran species, including triatomines, we suggest that the movement of rDNA loci from autosomes to sex chromosomes rapidly established reproductive barriers between divergent lineages. We proposed that the rDNA translocation from the autosomes to the sex chromosomes restrict reproductive compatibility and eventually promote speciation processes. We analyzed the chromosomal position of 45S rDNA clusters in almost all species of the matogrossensis, rubrovaria, maculata and sordida subcomplexes. The fluorescent in situ hybridization results are discussed considering the available genetic data and we proposed new arrangements in the species that constitute each one of these subcomplexes.
Keywords: Chagas disease vectors; FISH; Holocentric chromosomes; Location changes of rDNA clusters; Triatominae